Enhancing the performance and stability of NiCo2O4 nanoneedle coated on Ni foam electrodes with Ni seed layer for supercapacitor applications. Issue 10 (July 2019) - Park, Jiyoung; Ko, Tae Hoon; Balasubramaniam, Saravanakumar; Seo, Min-Kang; Khil, Myung-Seob; Kim, Hak-Yong; Kim, Byoung-Suhk
Abstract: We introduce a facile way to improve the performance of NiCo2 O4 electrode by including a Ni seed layer. The seed layer deposited on Ni foam electrode (NiCo2 O4 /Ni@NF) shows the superior specific capacity of 1142 C g −1 at 1 A g −1 with the excellent cycle stability of ∼96% even after 5000 cycles at a higher current density of 5 A g −1 . These values are about 3.7 times higher than that of the electrode (NiCo2 O4 @NF) without a seed layer, which shows the specific capacity of 305 C g −1 @1 A g −1 with cycle stability of 84% even at a lower current density of 1 A g −1 . The enhanced performance of the NiCo2 O4 /Ni@NF electrode may be attributed to lower interface resistance, fast redox reversible reaction, and improved surface active sites. Further, the asymmetric solid-state supercapacitor device is fabricated by using the NiCo2 O4 /Ni@NF electrode as a positive and reduced graphene oxide (rGO)-Fe2 O3 nanograin as a negative electrode with PVA-KOH gel electrolyte, and the NiCo2 O4 /Ni20@NF//rGO-Fe2 O3 @NF asymmetric solid state device delivers an areal capacitance of 446 mF cm −2 with a low capacitance loss of 18% even after 10000 cycles. Further, the fabricated asymmetric solid state device shows a maximum energy density of 124.3 Wh cm −2 (at 3.58 kW cm −2 ) and power density of 14.88 kW cm −2 (at 31.41 Wh cm −2 ). Graphical abstract: Image 1